Virological and Serological Discordant Profiles in COVID-19 Pneumonia: Two Atypical Clinical Cases - Ranzenigo, Martina; Pastori, Claudia; Siracusano, Gabriel; Pariani, Elena; Uberti-Foppa, Caterina; Lopalco, Lucia (Frontiers in Immunology, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is primarily diagnosed through viral RNA positivity in nasopharyngeal swabs, and it is associated with the early detection of specific immunoglobulins to SARS-CoV-2 proteins. We describe two moderate coronavirus disease 2019 (COVID-19) patients with WHO score 4/5 at the time of hospitalization, pneumonia, and oxygen saturation <94% and with a strong discrepancy between viral RNA and antibodies to SARS-CoV-2. One patient was positive for viral RNA but completely negative for binding and neutralizing antibodies, whereas the second patient was negative for viral RNA but with high levels of both neutralizing and binding antibodies. This observation is relevant to better understand the pathogenesis of this novel infection.